2015
DOI: 10.1177/0269216315575681
|View full text |Cite
|
Sign up to set email alerts
|

Dignity and patient-centred care for people with palliative care needs in the acute hospital setting: A systematic review

Abstract: Acute hospital staff require adequate training, including symptom control, and the correct environment in which to deliver dignified and person-centred end-of-life care. Specific models/approaches to care can be beneficial, if adequate training regarding implementation is given. The needs of family members also require consideration, particularly following bereavement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 77 publications
1
63
0
6
Order By: Relevance
“…A recent meta-synthesis of the palliative care experience in hospital, based on patient and caregiver narratives from 16 studies, identified 6 essential themes, seemingly applicable to all care settings: expert care, effective communication and shared decision making, respectful and compassionate care, adequate environment for care, family involvement, and financial affairs (Virdun et al, 2016). These authors report that these specified priories have remained consistent over time-also reflecting continuing gaps in this care (Cardona-Morrell et al, 2016;McCourt et al, 2013;Pringle et al, 2015;Robinson et al, 2014). The findings of these studies and ours characterize the optimal type of care that needs to be available to dying patients, regardless of setting, and sets a standard for system development.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-synthesis of the palliative care experience in hospital, based on patient and caregiver narratives from 16 studies, identified 6 essential themes, seemingly applicable to all care settings: expert care, effective communication and shared decision making, respectful and compassionate care, adequate environment for care, family involvement, and financial affairs (Virdun et al, 2016). These authors report that these specified priories have remained consistent over time-also reflecting continuing gaps in this care (Cardona-Morrell et al, 2016;McCourt et al, 2013;Pringle et al, 2015;Robinson et al, 2014). The findings of these studies and ours characterize the optimal type of care that needs to be available to dying patients, regardless of setting, and sets a standard for system development.…”
Section: Discussionmentioning
confidence: 99%
“…Palliative care is progressively documented as an important community service for end‐of‐life patients (Guo & Jacelon, ; Pringle, Johnston, & Buchanan, ), and palliative care nurses play a primary role in assisting care recipients (Johnston et al, ; McIlfatrick et al, ). Hence, nurses’ engagement and organisational commitment are pivotal to attentive caring for end‐of‐life patients (Freeney & Tiernan, ).…”
Section: Relevance To Clinical Practice: Nurses’ Work Engagement To Hmentioning
confidence: 99%
“…, Guo & Jacelon , Pringle et al . ). The need to provide care which is both responsive and supportive to individualised need is evidenced within the wide body of literature which associates the concept of a good death as one with dignity (Allmark , Yalden & McCormack , Guo & Jacelon ).…”
Section: Introductionmentioning
confidence: 97%
“…Dignity is a concept that pervades health policy, practice and biographical accounts of dying (Anderberg et al 2007). It is multifaceted and complex with various definitions in the literature, potentially contributing to a sense of confusion when applying and implementing dignity interventions in practice (Jacelon et al 2004, Guo & Jacelon 2014, Pringle et al 2015. The need to provide care which is both responsive and supportive to individualised need is evidenced within the wide body of literature which associates the concept of a good death as one with dignity (Allmark 2002, Yalden & McCormack 2010, Guo & Jacelon 2014).…”
Section: Introductionmentioning
confidence: 99%